The Right to Mental Health of Children in Cyberspace in the Light of the International Human Rights System - Seyednasseri, MohammadMehdi; Abbasi, Mahmoud (Bioethics and Health Law Journal (BHL), 2026)
The right to mental health is a fundamental component of the right to health and a core aspect of children’s rights. Among the factors influencing the realization or violation of this right, cyberspace plays a significant role, as children increasingly spend substantial time in digital environments that are often inappropriate for their age and mental development and may negatively affect their psychological well-being. Using a descriptive-analytical method, this study examines how children’s right to mental health can be realized in cyberspace in light of international human rights instruments. It analyzes key related rights in the digital context, including the rights to education, privacy, security, and play, and their connection to children’s mental health. The findings indicate that international human rights law, particularly in the field of children’s rights, provides comprehensive measures and obligations for States to protect children in the digital environment. Special attention is given to General Comment No. 25 (2021) of the UN Committee on the Rights of the Child, which clarifies States’ duties under the Convention on the Rights of the Child and its Optional Protocols in addressing the opportunities, risks, and challenges of the digital sphere, thereby affirming that children’s rights must be protected both offline and online.